Lexical Item Analysis in Speech by Unicef Executive Director Anthony Lake - Simatupang, Najmi Fara; Erlindawaty, Erlindawaty (Indonesian Journal Education, 2023)
This study deals in the lexical item analysis in Speech by UNICEF Executive Director Anthony Lake at the Harvard Conference on Adolescent Rights. This study aimed to find out the types of lexical item that focused on content word, function word and clause found in the Speech by Anthony Lake, to identify that often occurs on Speech by Anthony Lake, and to elaborate the reason for occurrence of dominant type in Speech by UNICEF Executive Director Anthony Lake at the Harvard Conference on Adolescent Rights. Descriptive qualitative research was applied in this study. The data of research were taken from Speech by Anthony Lake, 84 sentences found in this speech. The data were analyzed by identifying the speech into three types of lexical item in classifying the content word, function word and clause, analyzing the data into the each types of content word, function word and clause, calculating the types of content word, function word and clause, the most dominantly used in this speech, and finding the reason for occurrences of dominant type of content word, function word and clause on Speech by UNICEF Executive Director Anthony Lakeat the Harvard Conference on Adolescent Rights